"Żeby książka stała się powszechnie dostępna" - promocja czytelnictwa na łamach "Nadodrza" w latach 70. XX wieku = "So that books become widely available" - the promotion of reading in "Odra" in the 1970s - Podolan, Eligiusz (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
This article presents the journalism related to readership of the social-cultural magazine "Nadodrze" in Zielona Góra. During the period under consideration, despite the ongoing economic downturn, several events took place which contributed to the dissemination of activities promoting reading in the local society. This article present the views of Franciszek Pilarczyk, Grzegorz Chmielewski and Andrzej Krzysztof Waśkiewicz (pen name: Krzysztof Kościesz), who presented their own position as well as that of the scientific, library and journalist circles, in a professional and clear manner. The situation and the growing demands presented by them were intended to motivate dissidents and the public to minimize the negative factors affecting readership in the region.
Keywords: czytelnictwo; czasopisma; dostęp do kultury; książka; promocja czytelnictwa; Nadodrze (czasopismo); Chmielewski, Grzegorz; Pilarczyk, Franciszek; Waśkiewicz, Andrzej Krzysztof (1941-2012); reading; magazines; access to culture; book; promotion of reading